Prevalence of mupirocin resistance in methicillin-resistant Staphylococcus aureus strains isolated from a Malaysian hospital - Lim, K.T.; Hanifah, Y.A.; Mohd Yusof, M.Y.; Thong, Kwai Lin (Institute of Infectious Diseases, 2010)
Mupirocin is used topically to treat skin infection caused by methicillin-resistant Staphylococcus aureus (MRSA). One hundred eighty-eight strains (isolated in 2003, 2004, 2007, and 2008) were tested for mupirocin susceptibility using disk diffusion method and minimum inhibitory concentration (MIC). Mupirocin resistance was detected in 10 (5%) strains with 2 of them showing MIC of 256 mg/l. PCR detection using gene-specific primers showed that all 10 mupirocin-resistant strains harbored ileS2 gene whereas mupA gene was detected in 2 mupirocin-resistant strains with MIC of 256 mg/l. Amplification of agr grouping and SCCmec typing showed that all 10 strains were agr group I and SCCmec type III. Sequence analysis of region X of the spa gene yielded 4 distinct spa types (t037, t363, t421, and t6405) which were clonally related. In conclusion, the rate of mupirocin resistance in Malaysia is still low but is much higher than previous reports in Malaysia.